Procoagulant phenotype induced by oxidized high-density lipoprotein associates with acute kidney injury and death. Issue 223 (March 2023) - Prado, Yolanda; Pérez, Lorena; Eltit, Felipe; Echeverría, Cesar; Llancalahuen, Felipe M.; Tapia, Pablo; González, Pablo A.; Kalergis, Alexis M.; Cabello-Verrugio, Claudio; Simon, Felipe
Abstract: Background: Oxidative stress derived from severe systemic inflammation promotes conversion from high-density lipoprotein HDL to oxidized HDL (oxHDL), which interacts with vascular endothelial cells (ECs). OxHDL acquires procoagulant features playing a role in modulating coagulation, which has been linked with organ failure in ICU patients. However, whether oxHDL elicits a ECs-mediated procoagulant phenotype generating organ failure and death, and the underlying molecular mechanism is not known. Therefore, we studied whether oxHDL-treated rats and high-oxHDL ICU patients exhibit a procoagulant phenotype and its association with kidney injury and mortality and the endothelial underlying molecular mechanism. Methods: Human ECs, oxHDL-treated rats and ICU patients were subjected to several cellular and molecular studies, coagulation analyses, kidney injury assessment and mortality determination. Results: OxHDL-treated ECs showed a procoagulant protein expression reprograming characterized by increased E-/P-selectin and vWF mRNA expression through specific signaling pathways. OxHDL-treated rats exhibited a procoagulant phenotype and modified E-/P-selectin, vWF, TF and t-PA mRNA expression correlating with plasma TF, t-PA and D-dimer. Also, showed increased death events and the relative risk of death, and increased creatinine, urea, BUN/creatinine ratio, KIM-1, NGAL, β2M, and decreased eGFR, all concordant with kidney injury, correlated with plasma TF, t-PA and D-dimer. ICU patients showed correlation between plasma oxHDL and increased creatinine, cystatin, BUN, BUN/creatinine ratio, KIM-1, NGAL, β2M, and decreased GFR. Notably, ICU high-oxHDL patients showed decreased survival. Interestingly, altered coagulation factors TF, t-PA and D-dimer correlated with both increased oxHDL levels and kidney injury markers, indicating a connection between these factors. Conclusion: Increased circulating oxHDL generates an endothelial-dependent procoagulant phenotype that associates with acute kidney injury and increased risk of death.